Determinants of QRIS Adoption Among Students: The Roles of Knowledge, Ease of Use, Financial Literacy, and Perceived Benefits - Indriani, Rista; Valenty, Yola Andesta; Atmoko, Alfriadi Dwi (E-Jurnal Akuntansi, 2024)
This study addresses the phenomenon of a significant increase in QRIS usage in DIY (Daerah Istimewa Yogyakarta), despite its suboptimal adoption. The research aims to examine the influence of knowledge, ease of use, financial literacy, and perceived benefits on QRIS usage among students in DIY. Primary data were collected through a questionnaire distributed using a random sampling technique, with a total sample of 200 respondents. The analysis was conducted using multiple linear regression. The results indicate that knowledge and perceived benefits have a positive and significant impact on QRIS usage among students in DIY. Conversely, ease of use and financial literacy exhibit a positive but statistically insignificant effect on QRIS usage. However, when analyzed simultaneously, knowledge, ease of use, financial literacy, and perceived benefits collectively have a positive and significant effect on QRIS usage among students in DIY. The findings of this study contribute to existing literature by providing insights into the factors influencing QRIS adoption. These results serve as a valuable reference for future research and can support initiatives aimed at optimizing the use of QRIS, particularly among students.